IMPLEMENTATION OF DISTINCTION PRINCIPLE CONCERNING THE USE OF ARMED DRONES BY UNITED STATES OF AMERICA - Rauzatul Jannah; Sophia Listriani (Student Journal of International Law, 2021)
This study analyzes the legal problem regarding implementing the distinction principle related to drones as military weapons by the United States of America (USA) based on international humanitarian law. The method used in this research is normative legal research. The results show that implementing the distinction principle when the United States of America uses drones as military weapons is not correctly implemented, as international humanitarian law requires. It can be seen from the number of civilian casualties who fell during drone attacks and the destruction of civilian objects. So the USA has been violated the distinction principle of international humanitarian law, so legal liability must be pursued under the international justice system. Also, other states have to follow the principle when using to conform to international requirements, commit to solid criteria for disclosure, monitoring, and accountability, and release regular updates on drone strikes and casualties. Keywords: Distinction principle; International Humanitarian Law; Drones as military Weapon; United States of America